The Role of Parents in Fulfilling Nutrition and Respiratory Health for Children in Agricultural Area: Literature Review - Enggal Hadi Kurniyawan; Nur Hana; Muhammad Haidar Putra Kahono; Ifnadilla Ritma Sari; Alfid Tri Afandi; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur (KHD-Production, 2023)
Parents have a very important role in fulfilling the nutritional status of children. Lack of nutritional knowledge, especially in agricultural areas, influences food processing behavior so that nutritional problems in children tend to increase. This literature review aims to describe mother's knowledge, family support and risk factors for infectious diseases with nutritional status and respiratory problems in children in agricultural areas. Methods: This research uses the literature review study method with 4 databases, namely Google Scholar, PubMed, Scient Direct, and Springer with a range of 2019-2023. Result: The role of parents is related to nutritional status and health conditions in children. Parental education, inadequate environmental conditions, and potential risk factors can also affect the nutritional status and respiratory problems in children under five in agricultural areas. Babies born to mothers with low levels of education have a higher risk of experiencing health problems than babies born to mothers with higher education. The occurrence of ISPA in agricultural areas is caused by various environmental factors such as exposure to smoke and inadequate physical conditions of houses which can worsen indoor air quality. Potential risk factors that can cause STH infection are parental education and occupation, how to play on the ground, use of the toilet and how to wash hands. Nurses must provide support and education to people in agricultural areas related to providing nutritional intake, quality of living environment, and patterns of daily life in order to reduce problems with nutritional status and respiratory disorders in children.